2019
DOI: 10.22219/jinop.v5i2.9659
|View full text |Cite
|
Sign up to set email alerts
|

Rekognisi Dalam Merepresentasikan Simbol Turunan Parsial Sebagai Metonymy Dan Metaphor

Abstract: ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan kemampuan mahasiswa Teknik Sipil dalam merepresentasikan simbol sebagai metonymy dan metaphor melalui penyelesaian masalah Turunan Parsial. Instrumen penelitian yang digunakan adalah lembar observasi pembelajaran dan lembar worksheet berciri representasi matematis. Obervasi pembelajaran dilakukan ketika kegiatan pembelajaran dengan menggunakan worksheet berciri representasi matematis dilaksanakan. Worksheet berciri representasi matematis yang disajikan pada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Further, the errors committed by the research subjects were similar to those in another previous study. It was shown that the subjects could not interpret symbols holistically and precisely (Zukhrufurrohmah & Putri, 2019). In addition, the errors in designing mathematical models through mathematical symbols were also identical with a previous research that found the students' difficulties in designing mathematical model that fitted the given problems (Hidayah, 2016).…”
Section: Figure 5 the Error Committed By S2 In Interpreting Relational Operatorssupporting
confidence: 78%
See 2 more Smart Citations
“…Further, the errors committed by the research subjects were similar to those in another previous study. It was shown that the subjects could not interpret symbols holistically and precisely (Zukhrufurrohmah & Putri, 2019). In addition, the errors in designing mathematical models through mathematical symbols were also identical with a previous research that found the students' difficulties in designing mathematical model that fitted the given problems (Hidayah, 2016).…”
Section: Figure 5 the Error Committed By S2 In Interpreting Relational Operatorssupporting
confidence: 78%
“…In other words, metaphor offers an ease to learn mathematics more broadly (Malviya, 2019). According to a previous research about symbols as a metaphor, it showed that students were unable to represent symbols as a metaphor (Zukhrufurrohmah & Putri, 2019).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The partial derivative is the derivative of a function with respect to one variable, with the other variables constant (Zukhrufurrohmah & Putri, 2019). This allows us to understand how a function changes when one of its variables changes while the other variables stay the same.…”
Section: Lagrange Dynamics In Physical Mechanicsmentioning
confidence: 99%
“…Although partial derivatives are usually not introduced until a college-level calculus course, the concepts are relatively simple and can be explained to advanced high school students interested in learning more about calculus (Musyrifah, 2022). The partial derivative is the derivative of a function with respect to one variable, with the other variables constant (Zukhrufurrohmah & Putri, 2019). This allows us to understand how a function changes when one of its variables changes while the other variables stay the same.…”
Section: Lagrange Dynamics In Physical Mechanicsmentioning
confidence: 99%